The anterior head of deltoid in relation to anterior clavicle plating: how much are we releasing? - Sarah Black, MD; Tyler Snoap, MD; Eric Christiansen, MD; Jason Roberts, MD; Kevin A. Stehlík, BS (OTA International, 2022)
Objective:. Middle to distal-third clavicular shaft fractures are commonly treated with precontoured anterior plating. Some surgeons use mini-fragment plate fixation and position these plates on the anterior clavicle. Recent studies demonstrated the advantages of anterior clavicle plating, including a possible biomechanical advantage with cantilever bending forces and less subsequent implant removal. The insertion and positioning of anteriorly based clavicle plates requires the release of a portion of the anterior deltoid origin from the lateral clavicle. The purpose of this study is to evaluate the anatomy of the deltoid in relation to the clavicle and to determine the percentage of the deltoid origin released to place modern anterior precontoured plates. Methods:. Six right and 4 left cadaver shoulders were dissected, each from separate cadaveric specimens (6 male and 4 female). All measurements were made with digital calipers. The length of the clavicle was measured from the acromioclavicular joint to the sternoclavicular joint. The length of deltoid origin on the lateral clavicle was measured from the acromioclavicular joint to the most medial attachment of the deltoid on the clavicle. Percentage of clavicle with deltoid origin was subsequently calculated. Results:. The average length of the cadaveric clavicles was 164.4 mm with a range from 134.3 to 178.1 mm. The average amount of deltoid origin on the clavicle was 58.7 mm with a range from 43.4 to 69 mm. On average 35.5% of the clavicle had deltoid origin, with a range from 30.2% to 38.8%. Conclusion:. On average, 35.5% of the clavicular osseous anatomy contains deltoid origin. This should be taken into consideration when performing anterior plating for clavicle fractures. With a significant portion of deltoid origin elevated, surgeons may consider altering postoperative protocols until some interval healing has occurred to this anterior head of the deltoid.